1994
DOI: 10.1111/j.1600-051x.1994.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

A site‐by‐site follow‐up study on the effect of controlled versus poorly controlled insulin‐dependent diabetes mellitus

Abstract: In the present site-by-site follow-up study, the change in amount of approximal alveolar bone was assessed after 1 year from the baseline examination in 38 and after 2 years in 22 dentate subjects all with insulin-dependent diabetes mellitus. The diabetics, aged 35 to 56 years at baseline, had a history of a mean duration of 18 years of insulin-dependent diabetes mellitus and were under medical treatment at the outpatient clinic of the III Department of Medicine, University Central Hospital of Helsinki as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 23 publications
6
88
1
5
Order By: Relevance
“…Other meta-analyses indicated a statistically significantly higher mean clinical attachment loss (CAL) of 1 mm (P=0.02, 95% CI: 0.15-1.84) and a greater mean probing depth of 0.46 mm (P=0.05, 95% CI: 0.01-0.91) in patients with type 2 diabetes mellitus compared with controls. It can be summarized that poor glycemic control in patients with diabetes is associated with an increased risk of progressive loss of periodontal attachment and alveolar bone 20,21 . Although most research on the relationship between diabetes and periodontal disease has focused on mechanisms by which diabetes may affect periodontal status, a growing body of evidence has also examined the converse relationship; namely, how periodontal diseases may affect the metabolic state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other meta-analyses indicated a statistically significantly higher mean clinical attachment loss (CAL) of 1 mm (P=0.02, 95% CI: 0.15-1.84) and a greater mean probing depth of 0.46 mm (P=0.05, 95% CI: 0.01-0.91) in patients with type 2 diabetes mellitus compared with controls. It can be summarized that poor glycemic control in patients with diabetes is associated with an increased risk of progressive loss of periodontal attachment and alveolar bone 20,21 . Although most research on the relationship between diabetes and periodontal disease has focused on mechanisms by which diabetes may affect periodontal status, a growing body of evidence has also examined the converse relationship; namely, how periodontal diseases may affect the metabolic state.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between diabetes mellitus and periodontitis has appeared in the literature for over 70 years; however, with conflicting data. Numerous studies in various populations have demonstrated that individuals with diabetes tend to have a higher prevalence of and more severe periodontitis than nondiabetics 9 . Periodontal disease is the most prevalent oral complication in patients with type 2 DM (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic control of diabetes is considered to play the major role in determining the level of periodontal disease. Poorly controlled diabetic patients have more gingival inflammation, periodontal pockets and/or attachment loss than well-controlled diabetic patients (Ervasti et al 1984, Tervonen & Knuuttila 1986, Safkan-Seppälä & Ainamo 1992, Seppälä et al 1993, Tervonen & Oliver 1993, Seppälä & Ainamo 1994. But there are also studies in which no relation between periodontal disease and metabolic control is found (Bacic et al 1988, Hayden & Buckley 1989, Bridges et al 1996.…”
Section: Periodontal Diseasesmentioning
confidence: 98%
“…This finding was confirmed in a follow-up site-by-site study by the same authors. 50 The changes in the periodontal conditions are mostly expressed in the first year of the disease, and the damage to the periodontium which develops at this time is not greatly influeced in the further course of the disease (Fig 4). It is an interesting result that younger DM subjects display more periodontal destruction than do non-DM subjects at a later age.…”
Section: Risk Factor Influence On Periodontitis In Type 1 Dmmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Individuals with DM tend to have a higher prevalence of periodontal diseases and more severe and rapidly progressing forms than those who do not have DM. 41,48 DM is a known risk factor for periodontitis in adults.…”
Section: Risk Factor Influence On Periodontitis In Type 1 Dmmentioning
confidence: 99%